1989
DOI: 10.1111/j.1469-8749.1989.tb03978.x
|View full text |Cite
|
Sign up to set email alerts
|

Posture of Low‐risk Preterm Infants Between 32 and 36 Weeks Postmenstrual Age

Abstract: SUMMARY The supine posture of 15 low‐risk preterm infants was studied to establish whether they have a preferred posture and, if so, whether it changes with age. No over‐all preferred posture was found. Almost always one posture was adopted most frequently, but often a great variety of other postures were adopted almost as frequently. There was no correlation between postmenstrual age and preferred posture, the number of different postures, or the duration of longest uninterrupted posture. RÉSUMÉ Posture chez… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

1990
1990
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 5 publications
0
8
0
2
Order By: Relevance
“…There are obvious advantages to such a technique, but also disadvantages in the timeconsuming nature of both procedure and analysis, which preclude routine, daily clinical use. The same applies to the studies of Vles and colleagues (Vles 1988 , Vles el a/. 1989).…”
Section: Discussionmentioning
confidence: 79%
“…There are obvious advantages to such a technique, but also disadvantages in the timeconsuming nature of both procedure and analysis, which preclude routine, daily clinical use. The same applies to the studies of Vles and colleagues (Vles 1988 , Vles el a/. 1989).…”
Section: Discussionmentioning
confidence: 79%
“…However, the opposite is true. Detailed studies of motor behaviour of fetuses and newborn infants have shown that motility at early age is characterized by profuse variation, apparent in movement trajectories, and in temporal and quantitative aspects of motility 22,[39][40][41][42][43][44][45] , for example. These variations in motor activity are not neatly tuned to environmental conditions, but actually constitute a fundamental developmental phenomenon.…”
Section: Primary Variabilitymentioning
confidence: 99%
“…Human fetuses in utero assume flexion in the arms by 13 weeks, and in multiple limb joints by 20–28 weeks (Fong, Buis, Savelsbergh, & de Vries, ; Jirásek, ; Larsen, Sherman, Potter, & Scott, ). Flexion posture predominates by 36–37 weeks, with the hands contacting the face, and legs contacting the trunk (Casaer, ; Fong et al, ; Vles, Kingma, Caberg, Daniels, & Casaer, ). Semiflexed postures, presumed residual effects of prenatal constraints, may persist 1–10 days after full term birth (Beintema, ; Casaer, ; Dubowitz, Dubowitz, & Mercuri, ).…”
Section: Introductionmentioning
confidence: 99%